QMagFace: Simple and Accurate Quality-Aware Face Recognition - Terhörst, Philipp; Ihlefeld, Malte; Huber, Marco; Damer, Naser; Kirchbuchner, Florian; Raja, Kiran; Kuijper, Arjan (Proceedings of the IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

Lorenz Jaeger als Person

Dokumente und Deutungen. Interpretationsprobleme anhand eines Fallbeispiels von sexuellem Kindesmissbrauch in Kärnten 1939 - Priesching, Nicole; Hartig, Christine (Kirchliche Macht und kindliche Ohnmacht. Konturen, Kontexte und Quellen theologischer Missbrauchsforschung)

Missbrauchsforschung als Thema der Zeitgeschichte - Priesching, Nicole; Kleinehagenbrock, Frank (Historisches Jahrbuch)

Individualization of Public Transport – Integration of Technical and Social Dimensions of Sustainable Mobility - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fabian (Towards the New Normal in Mobility)
In order to follow the 1.5 degree path of the Paris Climate Agreement, drastic greenhouse gas reduction measures are needed in the transport sector. The potential of public transport and new mobility services to reduce transport-related greenhouse gas emissions cannot yet be fully exploited, especially in rural regions. This paper presents the concept of an innovative mobility system, called NeMo.bil, that intends to fill the gap between individual and public transport to create a demand-oriented and sustainable mobility offer. The concept is based on convoy formation of autonomously driving lightweight vehicles serving the first and last mile and a larger towing vehicle carrying enough power and energy to move the convoy over longer distances at higher speeds. This combination of two different vehicles, intelligently controlled by a digital ecosystem, aims to significantly increasing energy, resource and cost efficiency. Based on an analysis of previous approaches for innovative mobility solutions, the concept is derived from a technical and sociological perspective and its potential for reducing energy demand is calculated.

Introduction: Suffering and the Problem of Evil - Grössl, Johannes (T&T Clark Companion of Suffering and the Problem of Evil)

Der Gnadenstreit: Luis de Molina - Grössl, Johannes (Der Glaube im Denken. Eine Philosophiegeschichte)

The Impeccable Freedom of Christ - Grössl, Johannes (Theological Perspectives on Free Will: Compatibility, Community, Christology)

Zu den Anforderungen einer musikalischen Stilometrie - Kepper, Johannes
This is the extended abstract for my conference paper from the 2020 DHd Conference in Paderborn, along with the slides and moderator notes from the corresponding presentation.

DomesticBeethoven/bith-annotator: Release 2023-04 - Kepper, Johannes
This release covers the state of this prototype app at the end of the funding phase for the Paderborn University part of the Beethoven in the House project. It uses https://api.domestic-beethoven.eu/ld/BithCollection.jsonld as starting point for traversing the LOD graph, and reads data from the project pod available from https://bith.solidcommunity.net/public/bith.ttl (which has no content at the time of the release).
Keywords: MEI; Edirom; Music Encoding Initiative; Linked Open Data; MELD

MEI: The Music Encoding Initiative Guidelines (PDF)
PDF versions of the Music Encoding Initiative Guidelines 5.0 [2023]: This version represents the 5.0 release of the Music Encoding Initiative Guidelines.

Beethoven in the House: Selective Encodings of Arrangements of Beethoven’s opp. 91, 92, and 93. - Rosendahl, Lisa
This dataset contains selective MEI encodings of a number of arrangements of Beethoven’s Opp. 91, 92, and 93. These encodings were prepared in the context of the Beethoven in the House project, jointly funded by AHRC and DFG from 2020 to 2023. It is a slight update on v1.0.0 in better organizing the release assets.
Keywords: BitH; Dataset; Domestic Music Arrangements; Ludwig van Beethoven; MEI; Music Encoding Initiative

A New Conceptual Model for Musical Sources and Musicological Studies - Shibata, Elisabete; Lewis, David; Saccomano, Mark; Kepper, Johannes; Page, Kevin (Proceedings of the Music Encoding Conference 2022)
We present a new multi-layered, conceptual model for associating musical source materials to musicological arguments. We describe our proposal for operationalizing these concepts through a framework for musical annotation which we have implemented using RDF. Briefly stated, this model shows how portions of digitized data in various files and formats can be identified, selected, labelled, and compared.
Keywords: BitH; Linked Data

Supporting Musicological Investigations With Information Retrieval Tools: An Iterative Approach to Data Collection - Lewis, David; Shibata, Elisabete; Hankinson, Andrew; Kepper, Johannes; Page, Kevin R.; Rosendahl, Lisa; Saccomano, Mark; Siegert, Christine
Digital musicology research often proceeds by extending and enriching its evidence base as it progresses, rather than starting with a complete corpus of data and metadata, as a consequence of an emergent research need. In this paper, we consider a research workflow which assumes an incremental approach to data gathering and annotation. We describe tooling which implements parts of this workflow, developed to support the study of nineteenth-century music arrangements, and evaluate the applicability of our approach through interviews with musicologists and music editors who have used the tools. We conclude by considering extensions of this approach and the wider implications for digital musicology and music information retrieval.
Keywords: BitH; Linked Data

Temporal Sorting of Optical Multiwave-Mixing Processes in Semiconductor Quantum Dots - Grisard, Stefan; Trifonov, Artur V.; Rose, Hendrik; Reichhardt, Rilana; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (ACS Photonics)

Review of: Open Citizen Science: fostering open knowledge with participation. - Mauermeister, Sylvi (Research Ideas and Outcomes)

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)
Keywords: Arts and Humanities (miscellaneous); Education

Methodenentwicklung zur Verbesserung der Schädigungsmodellierung in der numerischen 3D-Belastungssimulation mechanischer Fügeverfahren unter Berücksichtigung der fügeinduzierten Vorbeanspruchung - Rossel, Moritz Sebastian; Meschut, Gerson; Bielak, Christian Roman; Otroshi, Mortaza

Geschichte der italienischen Zuwanderung nach Belgien im Medium Comic: Macaroni! (2016) und Une histoire importante. 70 ans d’immigration italienne en Belgique et plus (2019) - Schmitz, Sabine (Letteratura e migrazione/Literatur und Migration. Proposte intorno alla figura del ponte/ Fragen zur Figur der Brücke)

Lo fantástico en la escena del crimen: análisis del proceso de adaptación de la historieta El hipnotizador (2007) de Pablo de Santis y Juan Sáenz Valiente a la serie televisiva homónima de HBO Latin América (2015) - Schmitz, Sabine (Inter/Transmedialidad en el género negro y policial latinoamericano)